The change and clinical significance of the serum uric acid levels in patients with lupus nephritis - WANG Yi-ya; WU Yong-gui (Linchuang shenzangbing zazhi)
Objective To observe the serum uric acid levels in patients with lupus nephritis(LN)and explore its relationship with renal damage.Methods A retrospective analysis of the data of110 cases for nephrology renal biopsy and diagnosis of LN patients was made in the First Affiliated Hospital of Medical University of Anhui from January July 2015 to July 2017.The patients were divided into the two groups:LN patients with or without hypemricemia.All patients were collected for clinical pathological indicators,including age,gender,serum creatinine,urea nitrogen,serum uric acid,complement C3,complement C4,immunoglobulin A,immunoglobulin M,immunoglobulin G,24-h urine protein,anti-double-stranded DNA,-Smith,-SSA,-SSB,-RNP antibodies and pathological types,and scored for activity index,chronic index and systemic lupus erythematosus disease activity index.Results The clinical indicators,including the incidence rate of hypertension,level of blood serum creatinine and urea nitrogen,and the renal pathological scores,including acitive index and chronic index,in the LN patients with hyperuricemia group were higher than that in normal uric acid group,and estimate glomerular filtration rate was lower than that in normal uric acid group,the difference was statistically significant(P<0.05).However,there was no significant difference between the two groups in the other factors such as age,sex,complement C3,complement C4,immunoglobulin A,immunoglobulin M,immunoglobulin G,24-h urine protein,systemic lupus erythematosus disease activity index score and positive rate of anti-double-stranded DNA,-Smith,-SSA,-SSB,-RNP antibodies(P>0.05).Further analysis showed that the level of serum uric acid was positively correlated with serum creatinine,renal pathological classification and renal pathological scores,negatively correlate with estimate glomerular filtration rate(P<0.05).Conclusions LN patients with hyperuricemia had more severe renal damage than those in normal uric acid.Hyperuricemia is an important indicator for poor prognosis in patients with LN.